UTILIZATION OF SEABUCKTHORN FRUIT FOR THE PREPARATION OF GRANULES (Biological Sciences - PJSIR, 2003)
parameters of the process such as concentration of the pulp, temperature and time of drying, pH of concentrate, effect of various stabilizers and their concentration were optimized. Physico-chemical characteristics, nutritional and microbiological Seabuckthorn preserved fruit pulp of 11.8 ºBrix, procured from “Skardu”, was utilized for the preparation of granules. Various analyses of the pulp and the granules prepared were carried out. The product prepared from the pulp of 66 ºBrix dried in cabinet dryer at 50 ºC for 6 h resulted in the form of orange coloured granules which possessed a good taste, natural flavour and contained almost all the nutrients present in the fresh pulp.